Kekuatan Hukum Testament (Surat Wasiat) Terhadap Hak Mewaris Anak Angkat Menurut KUHPerdata - Amelia Niken Pertiwi; Dominikus Rato; Dyah Octhorina Susanti (Universitas Islam Darul Ulum, 2023)
In various regions in Indonesia, adopted children have the same legal status as their own children, including the right to be able to inherit wealth left by their adoptive parents when they die. In order to protect adopted children from continuing to obtain their rights over the inheritance of their adoptive parents, the parents make a will which is a way for the owner of the assets who during his lifetime expressed his last wish regarding the distribution of his inheritance to the heirs which will only take effect after he dies. In principle, people are free to determine their will for their assets after death. Likewise, the right to inherit adopted children is based on a will made by their adoptive parents so that the adopted child gets a share of the inheritance. Keywords : Inheritance, Will, Adopted Child